Influence of water-repellent admixtures on the properties of cements - Флейшер, Ганна Юріївна; Токарчук, Володимир Володимирович; Свідерський, Валентин Анатолійович (Technology audit and production reserves, 2015)
Influence of organic fatty acid and composition on its basis on the physical and mechanical properties of the cement is investigated. Fatty acids are used in the building industry as water-repellent admixtures. The effectiveness has those admixtures that form on the surface of the cement not solid, but "mesh" protective layer that easily destroyed using traditional method of cement production of concrete and mortar mixes, providing access of water to hydrophilic surface of cement grains. The effect of oleic acid on the physical and mechanical properties is investigated for a trade cement, clinker and Portland cement on its basis, slag and Portland slag cement on its basis. It is found that oleic acid gives hydrophobic properties for trade cement and Portland cement while slowing down the process of its thickening and gives small hydrophobic properties for blast furnace slag slowing down the thickening of Portland slag cement. It is researched an influence of hydrophobic compositions based on oleic acid and investigated admixture with food processing waste vegetable oil on physical and mechanical properties of Portland cement and Portland slag cement. It is found that hydrophobic composition effectively hydrophobize the clinker and slag surfaces under certain optimal concentrations without reducing strength of cements. Hydrophobic composition may be used as a water-repellent admixture for cement and active mineral admixtures to increase the longevity of materials and prevent clumping.